Fire-retardant effect of titania-polyurea coating and additional enhancement via aromatic diamine and modified melamine polyphosphate - Ze Rong (npj Materials Degradation, 2022)
Abstract Polymeric materials and composites are well suited to support structures in marine conditions due to their corrosion resistance. However, their low glass transition temperature makes them vulnerable to softening at high temperatures. Hence, fire retardancy is a key aspect if these materials are selected to ensure stiffness under flammable conditions. In this paper, a fire-retardant polyurea coating for industrial applications is proposed. The aromatic diamine and aliphatic diisocyanate are believed to have a synergistic effect in improving flame properties. Moreover, various combinations of flame-retardant additives with aromatic and aliphatic-based polyurea are mixed to further improve fire-retardancy. Through the characterizations of their glass transition temperature and delay in the ignition, it indicates that the combination of Talc and melamine polyphosphate may provide an outstanding enhancement for the Titania-polyurea coating, and such enhancement may improve its original tensile and compression strength, and surface hardness as well.